Research Of Autonomous Energy Supply Systems In Decentralized Energy Zones - Davlonov Khairulla Allamurodovich.; Sultanov Samandar Yamgirovich; Kudratov Jonibek Bakhodir ugli; Roziyeva Zarnigor Kahramonovna (Periodica Journal, 2024)
Based on renewable energy sources, it is aimed at analyzing and managing the optimal energy consumption of the autonomous energy system in the Kashkadarya region of the Republic of Uzbekistan. The main dimensions and parameters of a mobile home with an autonomous energy supply system based on completely alternative energy sources for heat and electricity consumers in areas far from centralized energy supply are presented. Based on the energy analysis of the traditional energy distribution systems of local consumers, the principle scheme of the mobile energy distribution system of local consumers was developed based on alternative energy sources. Processes for the formation of load schedules for autonomous consumers are provided. The average installed power and the critical minimum load of an autonomous residential building were determined, which do not exceed 20 kW and 2 kW, respectively. In order to save money when creating an autonomous generator complex, it is proposed to create a power supply system with heat load isolation
Keywords: Decentralized energy zones; autonomous energy system; optimal power consumption